Addiction to the Internet and Cyberbullying in Adolescents and Young Adults - Portilho Carvalho, Teresa; Carvalho Relva, Inês; Monteiro Fernandes, Otília (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
This study aimed to analyze the relationship between Internet addiction (measured using the Internet Addiction Test-IAT), victimization by cyberbullying (measured using the Cybervictimization Questionnaire- CYVIC) and aggression by cyberbullying (measured using the Cyber-aggression Questionnaire - CYBA). The sample consisted of 553 adolescents and young adults, aged between 17 and 30 years. We observed that 82.2% of participants had mild to moderate addiction to the Internet. The results show differences in terms of age, with adolescents being the age group most involved in cyber-victimization. They also suggest differences in the frequency of use of the Internet in relation to addicted use of the Internet, verifying that more hours of daily use of the Internet are related to the addictive use of the Internet. It was also possible to verify that the addition to the Internet is positively associated with cyber-victimization and cyber-aggression, and a positive association was found between cyber-victimization and cyber-aggression. Finally, there is a predictive effect of Internet addiction on both forms of cyberbullying. The need for greater attention on the part of health professionals regarding problems that arise in the virtual world is highlighted.